Survey of virtual network embedding problem - CHENG Xiang; ZHANG Zhong-bao; SU Sen; YANG Fang-chun (Tongxin xuebao)
Related research work of virtual networks（VN） embedding was surveyed,and both of the advantages and dis-advantages in the key technologies of related research work were analyzed.The possible future research directions were also discussed as references for the research of VN embedding problem.